Learning innovation for generation Z: development of e-modules and videos in research proposal courses - Aceng Jaelani; Wulan Andini; Heru Mudiyanto; Gusti Ristiani (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2025)
This study aims to develop e-modules and learning videos as learning media or resources in the Research Proposal course that can improve student understanding and engagement through a more interactive, practical, visual, and engaging digital approach for Generation Z students. The development process includes the creation of e-modules and videos, validation, and implementation of e-modules and videos. The research method used is Research and Development (RnD) with questionnaire and test data collection techniques. The population and sample in this study were 75 students majoring in Elementary Madrasah Teacher Education at UIN Siber Syekh Nurjati Cirebon. The results showed that the developed e-modules and videos were categorized as good (suitable for use). In addition, the use of e-modules and learning videos was effective in improving students' conceptual understanding, research skills, and learning motivation. This innovation not only facilitates access to materials but also encourages students to be more independent and active in the learning process. These findings indicate that e-module and video-based learning technology can be an effective solution for creating a more interactive and engaging learning experience in the context of higher education.